Application of the Standardized Precipitation Index (SPI) in Identifying Extreme Events - ZAMRI, KHAIRUNNISA; RAHMAT, SITI NAZAHIYAH (Recent Trends in Civil Engineering and Built Environment, 2021)
Extreme events such as drought and flood are the two of the most common extreme weather that take places in Malaysia. The Standardized Precipitation Index (SPI) is one of the indices used to quantify the precipitation deficit/excess for multiple timescales. The objectives of this study were to identify the historical extreme events using the SPI, to investigate the most appropriate combination of the SPI with its respective timescale and to identify the SPI trend analysis for the selected rainfall station. The data from 1978-2017 for eight (8) rainfall stations in Johor were selected for the computation of SPI. Based on the SPI values obtained, the number of wet and dry event were used in detecting the historical extreme events. It is shown that the past flood events happened in Johor in 2006 were related to the Northeast Monsoon while drought events that occurred in 1997 were related to the El Nino phenomenon. It is proved that the most appropriate SPI timescale was 12-month as it can be used to detect long term precipitation patterns. Lastly, the results from 12-month SPI values showed that five (5) stations had a decreasing trend while three (3) stations had an increasing trend. In conclusion, the results of this study can be used for future planning and forecasting of extreme events in Johor area.